Microbiological assessment of laboratory rodents: Perspectives from laboratory animal facility of ACTREC (Journal of Laboratory Animal Science, 2024)
Detection of pathogenic organisms in any module of the conventionally bred animal facility is suggestive  of possible infection in other strains/ modules of the facility as well. Timely diagnosis of the microbes  prevailing in the conventional animal facility is possible if well planned screening program is in place.  Laboratory Animal Facility of ACTREC breed and maintains 22 different strains of mice, two strains of  hamsters and one rat strain. This paper report the microbiological screening results of rodent pathogens  prevailing in the Laboratory animal Facility, ACTREC, India. Microbiological status of these strains was  assessed by conventional microbiology using agar media and biochemical tests; readymade ELISA kits and  PCR methods. Results of the conventional microbiology revealed that the rodents in ACTREC were reported  positive for Klebsiella pneumoniae, Staphylococci aureus, Escherichia coli and Proteus sp. Recent ELISA based  results revealed presence of Mycoplasma pulmonis, CAR bacilli, Sendai, Tyzzer’s disease, MHV, Helicobacter  hapaticus, Polyoma, Minute virus of mice, Pneumocystis carinii, Pasturella pneumotropica and Mouse  Parvovirus; whereas PCR based methods revealed presence of Mycoplasma pulmonis, Sendai, Helicobacter  hapaticus, Pneumocystis carinii, Helicobacter bilis, MNV, MHV and CAR bacilli. Effective quarantine, barrier  maintenance, frequent surveillance for all recommended pathogens and eradication of the existing  pathogens is the challenge to be accepted.
Keywords: ACTREC; microbial status; pathogen; rodents